Pre-existing type 2 diabetes and risk of lung cancer: a report from two prospective cohort studies of 133 024 Chinese adults in urban Shanghai - Yang, Wan-Shui (BMJ Publishing Group, 2014)
OBJECTIVES: Observational studies of type 2 diabetes (T2D) and lung cancer risk are limited and controversial. We thus examined the association between T2D and risk of incident lung cancer using a cohort design. SETTING: Data from two ongoing population-based cohorts (the Shanghai Men's Health Study, SMHS, 2002–2006 and the Shanghai Women's Health Study, SWHS, 1996–2000) were used. Cox proportional-hazards regression models with T2D as a time-varying exposure were modelled to estimate HRs and 95% CIs. PARTICIPANTS: The study population included 61 491 male participants aged 40–74 years from SMHS and 74 941 female participants aged 40–70 years from SWHS. OUTCOME MEASURE: Lung cancer cases were identified through annual record linkage to the Shanghai Cancer Registry and Shanghai Municipal Registry of Vital Statistics, and were further verified through home visits and a review of medical charts by clinical and/or pathological experts. Outcome data until 31 December 2010 for men and women were used for the present analysis. RESULTS: After a median follow-up of 6.3 years for SMHS and 12.2 years for SWHS, incident lung cancer cases were detected in 492 men and 525 women. A null association between T2D and lung cancer risk was observed in men (HR=0.87, 95% CI 0.62 to 1.21) and women (HR=0.92, 95% CI 0.69 to 1.24) after adjustments for potential confounders. Similar results were observed among never smokers. CONCLUSIONS: There is little evidence that pre-existing T2D may influence the incidence of lung cancer.